1996
DOI: 10.1113/expphysiol.1996.sp003950
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of the endogenous L‐arginine analogue NG‐monomethyl‐L‐arginine in human end‐stage renal failure patients on regular haemodialysis

Abstract: SUMMARYWe measured plasma levels of L-arginine, its analogue NG-monomethyl-L-arginine (L-NMMA), and related amino acids in normal subjects and uraemic patients (n = 31), before and after haemodialysis. Plasma levels of L-arginine were reduced to less than half of normal values in uraemic subjects compared with controls, and were not affected by haemodialysis. L-NMMA was not detectable in non-uraemic subjects, but markedly elevated in uraemic patients. In parallel, we used human red blood cells as a model to st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 9 publications
1
17
0
Order By: Relevance
“…As the kidney is involved in regulating circulating arginine concentrations, potential derangement of arginine metabolism could occur in end-stage renal failure. This has been shown in dialysis patients where plasma citrulline concentrations are high and arginine concentrations low [22,23]. This, however, may not be physiological relevant, as arginine transport into cells is increased in uraemia [24,25].…”
Section: Scheme 1 Inhibition Of Arginase By Uraemia Results In Increamentioning
confidence: 95%
“…As the kidney is involved in regulating circulating arginine concentrations, potential derangement of arginine metabolism could occur in end-stage renal failure. This has been shown in dialysis patients where plasma citrulline concentrations are high and arginine concentrations low [22,23]. This, however, may not be physiological relevant, as arginine transport into cells is increased in uraemia [24,25].…”
Section: Scheme 1 Inhibition Of Arginase By Uraemia Results In Increamentioning
confidence: 95%
“…In ESRD patients, the short-term effect of a single HD session on the plasma levels of l-arginine has been extremely variable between studies, with some finding no change [27,28,32,38] while others reported decreases ranging from 10-70 % of pre-dialysis values [26,[39][40][41]. The present study clearly belongs to the second category (Figure 2), although the results differed considerably between patients, possibly because of a variable redistribution of l-arginine between intracellular and extracellular pools (keeping in mind that the former is by far the larger) [42].…”
Section: Acute Impact Of Hdmentioning
confidence: 99%
“…17,33 Concentrations of L-NMMA in healthy controls appear to be 10 times lower than that of ADMA 17,34 but are increased significantly (1.4ϫ10 Ϫ5 mol/L) in uremic patients. 34 These values in uremic patients are within the range of concentrations tested in the present study. Plasma ADMA levels in normotensive and hypertensive rats (0.7ϫ10 Ϫ6 mol/L) 25 are similar to those observed in healthy volunteers.…”
Section: Discussionmentioning
confidence: 99%